Disrupted Development and the Future of Inequality in the Age of Automation - Schlogl, Lukas. author. aut Link
XIII, 102 p. 13 illus., 12 illus. in color.
Keywords: "A piece of cutting-edge scholarship, this book examines the relationship between robotization and deindustrialization by looking at the global dynamics of job displacement and its likely effect on economic development. Schlogl and Sumner argue convincingly that developing countries face a growing informal, precarious service sector in the age of automation." —Ray Kiely, Professor of International Politics, Queen Mary University of London, UK This open access book examines the future of inequality, work and wages in the age of automation with a focus on developing countries. The authors argue that the rise of a global ‘robot reserve army’ has profound effects on labor markets and economic development, but, rather than causing mass unemployment, new technologies are more likely to lead to stagnant wages and premature deindustrialization. The book illuminates the debate on the impact of automation upon economic development,in particular issues of poverty, inequality and work. It highlights public policy responses and strategies–ranging from containment to coping mechanisms—to confront the effects of automation. Lukas Schlogl is a political scientist in the Department of Political Science, University of Vienna, Austria. Andy Sumner is Professor of International Development in the Department of International Development at King’s College London, UK.